2010
DOI: 10.1242/jeb.029959
|View full text |Cite
|
Sign up to set email alerts
|

Substratum cavities affect growth-plasticity, allometry, movement and feeding rates in the sea urchinStrongylocentrotus purpuratus

Abstract: SUMMARYWe assessed the influence of rock cavities, or pits, on the growth dynamics and behavior of the purple sea urchin, Strongylocentrotus purpuratus. In a paired-designed, laboratory experiment, sea urchins were assigned to sandstone blocks that were either 'Flat' or had a 'Pit' drilled into the center. At the start, both groups were approximately the same shape and size. In just 2 months, the shapes of the tests were significantly different between the two treatments, with the Pit urchins having an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 49 publications
(57 reference statements)
2
16
0
1
Order By: Relevance
“…In turn, the adult animals are responsible for the large, groove-like borings produced when it bores slowly forward while grazing on algae. This is confirmed with experiments made by Hernández and Russel (2010), who observed that many sea urchins with identical food availability, such as Echinometra mathaei, Strongylocentrotus droebachiensis, S. purpuratus or Paracentrotus lividus, change their morphology during growth owing to the microhabitat conditions occupied (presence or absence of a cavity).…”
Section: Movement Pattern Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…In turn, the adult animals are responsible for the large, groove-like borings produced when it bores slowly forward while grazing on algae. This is confirmed with experiments made by Hernández and Russel (2010), who observed that many sea urchins with identical food availability, such as Echinometra mathaei, Strongylocentrotus droebachiensis, S. purpuratus or Paracentrotus lividus, change their morphology during growth owing to the microhabitat conditions occupied (presence or absence of a cavity).…”
Section: Movement Pattern Analysissupporting
confidence: 84%
“…Circolites reproduces a dwelling structure where sea urchins are protected from predators and wave surge and where occasionally they act as macro-suspension feeders trapping organic material brought into the boring by the rising tide (Asgaard and Bromley, 2006). Hernández and Russel (2010) also attribute to these pits a more hospitable microhabitat by retaining water and moderating temperatures and desiccation during emersion at low tide. Ericichnus igen.…”
Section: Movement Pattern Analysismentioning
confidence: 99%
“…Sea urchins lack fast escape and are able to acclimate to a new environment by modulating their morphology and physiology. For example, it was shown that Strongylocentrotus purpuratus is able to reshape its skeleton and change its behavior in a matter of 8-20 weeks when exposed to a different habitat structure (Hernández and Russell 2010). As a consequence, short-term exposure may both over-(no acclimation) and underestimate (not enough time to induce lethal effects) the real impacts of a chronic exposure to high pCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Changes in jaw and diameter allometry also have been induced under laboratory conditions of food manipulations in S. purpuratus [18,33,34], S. droebachiensis [24,35], M. franciscanus [36,37], D. antillarum [27], Paracentrotus lividus [38] and Lytechinus variegatus [39].…”
Section: Introductionmentioning
confidence: 99%